PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 s.d 2014 - Sianturi, Rahmat; ', Makhdalena; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrac: This study aims to examine the effect of disclosure of Corporate Social Responsibility on the financial performance proxied by Return on Assets (ROA) and Return On Equity (ROE) in the banking companies listed in Indonesia Stock Exchange period 2013 to 2014. The company's total banking sector is 37 companies. Companies that have the necessary data in this study is 22 companies. Data analysis techniques used in this research is simple regression analysis techniques. The result showed that the disclosure of corporate social responsibility affect the return on assets of 16.3%, further disclosure of corporate social responsibility affect the return on equity of 45.3%. Key Words: Corporate social responsibility, return on asset, return on equity